1994
DOI: 10.1007/bf01627685
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of posteromedial and posterolateral stabilisers of the knee: anatomic basis and patterns of lesions in knee injuries

Abstract: The angular points are the ligamentous and tendinous structures that reinforce the posteromedial and posterolateral capsule of the knee and share in fixation of the posterior horns of the menisci. They are often damaged in acute injuries and this is usually associated with ruptures of the cruciate and collateral ligaments and may add to the degree of laxity. We describe the normal appearance of these structures in terms of the sectional anatomy, correlated with the lesional appearances of complete and incomple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…LaPrade et al [21, 26] recommended a field of view that included the fibular head and styloid on all projections and demonstrated that MRI was accurate in depicting the integrity of the individual components of PLC in 20 patients with high‐grade PLRI. A problem with MRI, however, is that it has low credibility in chronic injury cases [12, 39].…”
Section: Discussionmentioning
confidence: 99%
“…LaPrade et al [21, 26] recommended a field of view that included the fibular head and styloid on all projections and demonstrated that MRI was accurate in depicting the integrity of the individual components of PLC in 20 patients with high‐grade PLRI. A problem with MRI, however, is that it has low credibility in chronic injury cases [12, 39].…”
Section: Discussionmentioning
confidence: 99%